Exploration for lithium deposits in the Barroso-Alvao area, Northern Portugal - Lima, A (1999)
Results of a multidisciplinary study on lithium-rich pegmatites-aplite veins are presented. These results confirm the economic importance of the Banoso-Alvao area (North of Portugal). Dense swarms of pegmatite-aplites veins are encountered in metasedimentary rocks, Silurian in age, and define an almost 20 km alignment parallel to the regional Hercynian structural trend. Spodumene, with subordinate petalite, forms the main economic minerals. Subsolidus feldspar and/or muscovite alteration is the rule, with the large decrease of Li (only eucryptite in small amount is growing) which is leached out of the system. These pegmatite bodies appear to be of good quality for the ceramic industries.